Pengaruh Kesiapan Belajar dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi pada Siswa Kelas X IPS SMA Negeri 1 Batang Angkola - Sari, Erlina; Ritonga, Mariyatul Kubtiyah (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This study aims to prove is there a significant influence between learning readiness and learning motivation simultaneously and partially on the learning outcomes of the student economics in class X SMA Negeri 1 Batang Angkola. The method used is descriptive method. Data collections technique using questionnaries and documentation. The data analysis technique used is simple and multiple linier regression test with the help of SPSS version 26.00. the results obtained prove that Fhitung is 9,479 with a value sig 0,001 while the Ftabel value at the 95% (Î± = 0,05) is 3,28. Therefore, in both calculation, i.e F hitung F tabel (9,479 3,28) and value sig(0,001 0,05) shows that there is a simultaneous and partial effect of learning readiness and learning motivation on the learning outcomes of economic subjects in class X IPS SMA N 1 Batang Angkola. This means that the better students learning readiness and the higher the motivation to learn, the higher the learning outcomes achieved. Learning readiness and learning motivation are learning principle that can affect student learning outcomes. With good learning readiness and followed by high learning motivation it will produce good learning outcomes. Motivation will form awareness and good learning readiness causing studens to learn actively